Digital Marketing Strategy Through Social Media at Arunika Eatery, Kuningan - Sudiana Wachyudi; Widia Ningsi; Gina Aulia Salsabila (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Each business has its marketing strategy. In the digital era, utilizing social media become part of the marketing strategy that every single business has used. Through social media, businesses can reach out to various types of customers and decide who will be their customers. This study aims to find out how digital marketing strategies in Arunika Eatery, Kuningan, increasing consumer purchases, the types of marketing content that can increase the promotion of Arunika Eatery, Kuningan, and what the supporting and inhibiting factors in marketing their products through social media. The method used is qualitative descriptive. Data collection techniques through observation, interviews, and literature studies. Arunika Eatery, Kuningan, has implemented a digital marketing strategy through social media with a 70-20-10 strategy. Arunika Eatery, Kuningan carries out its marketing strategy with diverse and exciting content, which contains event promotions carried out by Arunika Eatery Kuningan, information about Arunika Eatery Kuningan, short videos, quotes, and question and answer sessions to its followers. This research focuses on the analysis of marketing strategy for the food and beverages business, especially in the Kuningan area. The researcher is the first one to conduct research about Arunika Eatery, and there's no previous research.